The Big Three and corporate carbon emissions around the world - Azar, José; Duro, Miguel; Kadach, Igor; Ormazabal, Gaizka (Journal of Financial Economics, 2021)
This paper examines the role of the “Big Three” (i.e., BlackRock, Vanguard, and State Street Global Advisors) on the reduction of corporate carbon emissions around the world. Using novel data on engagements of the Big Three with individual firms, we find evidence that the Big Three focus their engagement effort on large firms with high CO2 emissions in which these investors hold a significant stake. Consistent with this engagement influence being effective, we observe a strong and robust negative association between Big Three ownership and subsequent carbon emissions among MSCI index constituents, a pattern that becomes stronger in the later years of the sample period as the three institutions publicly commit to tackle Environmental, Social, and Governance (ESG) issues.